The geochemistry and petrology of the upper critical zone in the boshoek section, of the Western Bushveld complex - Von Gruenewaldt, G. (Gerhard), 1942- (University of Pretoria, 2024)
Dissertation (MSc (Geology))--University of Pretoria, 1991.